Effects of post-heat treatment on microstructure and properties of laser cladded composite coatings on titanium alloy substrate. (January 2015) - Li, G.J.; Li, J.; Luo, X.
Abstract: The composite coatings were produced on the Ti6Al4V alloy substrate by laser cladding. Subsequently, the coatings were heated at 500 °C for 1 h and 2 h and then cooled in air. Effects of post-heat treatment on microstructure, microhardness and fracture toughness of the coatings were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), optical microscopy (OM). Wear resistance of the coatings was evaluated under the dry sliding reciprocating friction condition at room temperature. The results indicated that the coatings mainly consist of a certain amount of coarse white equiaxed WC particles surrounded by the white-bright W2 C, a great deal of fine dark spherical TiC particles and the matrix composed of the α (Ti), Ti2 Ni and TiNi phases. Effects of the post-heat treatment on phase constituents and microstructure of the coatings were almost negligible due to the low temperature. However, the post-heat treatment could decrease the residual stress and increase fracture toughness of the coatings, and fracture toughness of the coatings was improved from 2.77 MPa m 1/2 to 3.80 MPa m 1/2 and 4.43 MPa m 1/2 with the heat treatment for 1 h and 2 h, respectively. The mutual role would contribute to the reduction in cracking susceptibility. Accompanied with the increase in fracture toughness, microhardness of the coatings was reduced slightly. The dominant wear mechanism for all the coatings was abrasive wear, characterized by micro-cutting or micro-plowing. The heat treatment could significantly decrease the average friction coefficient and reduce the fluctuation of the friction coefficient with the change in sliding time. The appropriate heat treatment time (approximately 1 h) had a minimal effect on wear mass loss and volume loss. Moreover, the improvement in fracture toughness will also be beneficial to wear resistance of the coatings under the long service. Highlights: TiC+WC reinforced intermetallic compounds matrix composite coatings were produced. The formation mechanism of the reinforcements was analyzed. Cracking susceptibility of the coatings was decreased. Heat treatment reduced average value and fluctuation of the friction coefficient. Appropriate post-heat treatment is help to improve wear resistance of the coatings.